2021
DOI: 10.1177/09544054211001014
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization of the actively driven rotary turning for energy efficiency, carbon emissions, and machining quality

Abstract: Boosting energy efficiency and machining quality are prominent solutions to achieve sustainable production for turning operations. In this work, a machining condition-based optimization has been performed to decrease the total specific energy (SEC), carbon emission (CE), and average roughness (AR) of the actively driven rotary turning (ADRT) process. The processing factors are the tool rotational speed (Tv), depth of cut (a), feed rate (fr), and workpiece speed (Wv). The turning experiments of the mold materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The carbon emissions of each reworked or scrapped product are multiplied by that percentage so that the number of saved carbon emissions can be converted and calculated. In addition to lessening carbon emissions, this process can lower the cost of loss caused by reworking or scrappage and increase the value of the product [23,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon emissions of each reworked or scrapped product are multiplied by that percentage so that the number of saved carbon emissions can be converted and calculated. In addition to lessening carbon emissions, this process can lower the cost of loss caused by reworking or scrappage and increase the value of the product [23,28].…”
Section: Discussionmentioning
confidence: 99%
“…Improving process quality can decrease the ratios of reworking and scrappage during the process of production, as well as reduce the frequency of maintenance or replacement after purchase. Consequently, not only does this lessen the cost of rework, scrap, and maintenance, as well as the harm caused by environmental pollution, but it also contributes to the sustainability of enterprises and that of the environment [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many well-known sports brands are proactively developing new products highlighting high functionality, environmental friendliness, and pleasing appearance. In addition, plenty of research has also indicated that good process quality can not only improve product yield and product value but also lower rates of rework and scrap [1][2][3]. Since enterprises are confronting the regulatory pressure of green environmental protection and competition from external rivals, they need to contemplate how to boost the quality of newly developed products, increase product value, and minimize Mathematics 2024, 12, 1446 2 of 11 rates of both rework and scrap to reach the goals of conserving energy and reducing waste.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have pointed out that improving the process quality of the product can reduce an increase in the cost expenditure caused by the reworks of defective products as well as can lower energy loss and carbon emissions [8][9][10][11]. According to the concept of Taguchi loss function, when the process quality of components for machining machines is not good and the size of the processed product deviates too far from the target value, the failure rate of the product will rise after the product is sold.…”
Section: Introductionmentioning
confidence: 99%